The effect of the association between food budget and food quality on adherence to national guidelines in kindergartens, and the impact of budget limit on the food quality - Kristin E. Fjæra; Ratib Lekhal; Sølvi Helseth; Milada Hagen; Samira Lekhal (Food & Nutrition Research, 2024)
Background: In Norway, almost 97% of children attend kindergartens. Most of the daily food intake happens during the day in kindergartens, and the quality of food and meals being served is essential to promote healthy food habits. There is variation in the food that kindergartens provide, and kindergartens can ask for additional payment from parents to cover the food. There are no rules neither across kindergartens for the food offering nor how much additional payment kindergarten can request. Objective: Our main objective is to investigate possible associations between the food budget and the quality of food offered in kindergartens. We specifically aimed to identify budget levels that were associated with better adherence to national guidelines, thereby the quality of the food provided, as recommended by the Norwegian Directorate of Health. Design: A cross-sectional study design, based on kindergarten pedagogical leaders’ answers to a web-based questionnaire. Settings: Private and public kindergartens across Norway are included in this present study. Participants: A total of 324 kindergarten staff attending on behalf of kindergartens participated. Results: The food budget thresholds over NOK 199 are associated with higher quality of served food, in adherence to national guidelines of food and meals (odds ratio 5.2, CI = [1.5, 16.5]), compared to thresholds under 199 NOK. However, increasing the monthly food budget per child to low (200–299 NOK), medium (300–399 NOK), high (400–499 NOK), or very high (>500 NOK) levels did not lead to an improvement in food quality. Conclusion: The main results reveal that budget plays a limited role in the quality of food and meals served as long as it is above ‘very low’ (199 NOK) food budget threshold. We assume that other contextual factors can influence the quality of food and meals in a more prominent role.